Pengembangan Bahan Ajar Digital Interaktif Keterampilan Menyimak Bermuatan Pembelajaran Mendalam pada Pembelajar Bahasa Indonesia Bagi Penutur Asing - Yulia Nadhira; Safinatul Hasanah Harahap; Surya Masniari Hutagalung (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to (1) describe the process of developing interactive digital listening materials integrating deep learning for Level 1 learners of Indonesian for Foreign Speakers (BIPA), (2) produce interactive digital listening materials integrating deep learning for Level 1 BIPA learners, (3) determine the feasibility of the developed instructional materials, and (4) determine their effectiveness in improving the listening skills of Level 1 BIPA learners. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results showed that the development process was carried out through the stages of needs analysis, product design, material development, implementation, and evaluation. The resulting product was interactive digital listening materials consisting of seven learning units, namely self-introduction, family, food, traditional clothing, tourist attractions, daily activities, and public places and directions. The materials were equipped with audio recordings, interactive exercises, immediate feedback, scoring features, answer keys, discussion forums, and reflective activities integrated with deep learning principles. The validation results indicated that the instructional materials were categorized as highly feasible, with a material expert assessment score of 96.3%. The design expert validation yielded a score of 98.4%, BIPA instructor responses reached 90.9%, individual trial results obtained 88.9%, and field trial results reached 88.6%, all of which were categorized as highly feasible. The effectiveness of the instructional materials was demonstrated by the improvement in learners’ achievement scores between the pretest and posttest after using the developed materials. The mean pretest score of 79.2 increased to 92.2 on the posttest. The N-Gain test yielded an average score of 0.63 or 63%, which falls into the moderately effective category. Overall, the results indicate that the developed interactive digital listening materials integrating deep learning are highly feasible and moderately effective for use as supplementary instructional materials in Level 1 BIPA learning. These materials can serve as an alternative learning resource that supports the improvement of listening skills and promotes active learner engagement in the learning process of Indonesian for Foreign Speakers.